Association between LXR-α and ABCA1 Gene Polymorphisms and the Risk of Diabetic Kidney Disease in Patients with Type 2 Diabetes Mellitus in a Chinese Han Population. (22nd December 2020) - Liu, Peng; Ma, Liang; Zhao, Hailing; Shen, Zhengri; Zhou, Xuefeng; Yan, Meihua; Zhao, Tingting; Zhang, Haojun; Qiu, Xinping; Li, Ping
Abstract : We designed a case-control study and selected LXR-α rs7120118 C>T and ABCA1 rs2230806 A>G polymorphisms to determine the correlation between these polymorphisms and diabetic kidney disease (DKD) susceptibility in a Chinese Han population. Three hundred DKD patients and 346 type 2 diabetes mellitus (DM) patients without kidney disease were recruited. Our results showed that rs7120118 was associated with DKD (genotype, P = .027 ; allele, P < .011 ). rs7120118 was associated with a higher risk of DKD under a dominant model adjustment by age and sex (P = .015 ) and an additive model (P = .040 ); rs2230806 was associated with a higher risk of DKD under an recessive model (P < .03 ); the combined effect of rs7120118 CC+rs2230806 GG genotype showed an association of DKD adjustment for age and sex (P = .009 ). In subgroup analysis of patients without hypercholesterolemia, the rs2230806 genotype frequencies were different between the two groups (P = .042 ). rs2230806 was associated with increased risk of DKD under a recessive model adjustment for age and sex (P = .013 ) and an additive model (P = .031 ). Our results suggest that LXR-α rs7120118 is significantly associated with a higher risk of DKD, and ABCA1 rs2230806 is significantly associated with a higher risk of DKD without hypercholesterolemia in Chinese Han individuals.